Nosocomial COVID-19: experience from a large acute NHS Trust in South-West London. Issue 3 (November 2020) - Taylor, J.; Rangaiah, J.; Narasimhan, S.; Clark, J.; Alexander, Z.; Manuel, R.; Balasegaram, S.
SUMMARY: Transmission of coronavirus disease 2019 (COVID-19) in healthcare settings has significant implications for patients and healthcare workers, may amplify local outbreaks, and may place additional burden on already stretched resources. Risk of missed or late diagnosis of COVID-19 was high during the UK's initial 'containment phase', because of strict criteria for testing. The risk remains due to asymptomatic/pre-symptomatic transmission, complicated by challenges faced with laboratory testing. We present a case study of potential nosocomial transmission associated with the first case of COVID-19 at a large acute NHS Trust in South-West London, and we describe the prevailing burden of nosocomial infections.